Artificial Intelligence (AI) in Islam: Building Ethics and Solutions Based on Tawhid - Mamdukh Budiman; Mirza Mahbub Wijaya; Rijal Wakhid Rizkillah; Iqbal Hidayatsyah Noor; Safuan Safuan; Rachmat Destriana (Proceeding of The International Conference on Religious Education and Cross - Cultural Understanding, 2025)
This article explores the application of Islamic ethics, particularly the concept of tawhid, in the development of digital technologies and artificial intelligence (AI). The study employs a qualitative descriptive method based on a literature review to analyze Islamic principles, such as justice (al-'adl), trust (amanah), and public benefit (al-maslahah), in addressing ethical challenges posed by AI. The findings indicate that Islamic values can provide a holistic framework for tackling algorithmic bias, privacy concerns, and social inequalities associated with AI. However, the study identifies a gap in academic research regarding the integration of tawhid principles with AI development. A limitation of this research is the lack of empirical case studies to test the effectiveness of implementing these principles in technology development.